NILAI PERSONAL DALAM CERITA PALAYA SUBETNIK KATINGAN - Theresia Dessy Wardani (Universitas Lambung Mangkurat, 2018)
AbstractPersonal Values in Story of Palaya from Katingan Subethnic. Palaya is a community folklore of Katingan sub-ethnic whish is one of the literary works owned by the community of Katingan Tengah sub-ethnic. This study focuses on personal values which include: (1) emotional value, (2) moral value, and (3) Social value. There were 20 personal values found in the story of Palaya, the Katingan sub-ethnic which consist of expression of joy, sadness, fear, shympaty and emphaty, hatred and revenge. There were 16 moral values found in the story of Palaya, the Katingan sub-ethnic, they were respectful, devoted, patient, brave, honest, and wise. There were 10 social values found in the story of Palaya, the Katingan sub-ethnic, they were cooperative attitude, mutual help, doing cooperative activities, helping to overcome difficulties others.Key words: emotional value, moral value, social value, Palaya, story sub-ethnic KatinganAbstrakNilai Personal dalam Cerita Palaya Subetnik Katingan. Palaya adalah dongeng masyarakat subetnik Katingan yang merupakan salah satu bentuk sastra yang dimiliki oleh masyarakat subetnik Katingan Tengah. Penelitian ini difokuskan pada nilai personal yang meliputi: (1) nilai emosional, (2) nilai moral, dan (3) nilai sosial. Nilai personal yang terdapat pada cerita palaya subetnika Katingan berjumlah dua puluh yang terdiri dari ekspresi gembira, sedih, takut, simpati dan empati, benci dan dendam. Nilai moral yang terdapat pada cerita palaya subetnika Katingan berjumlah enam belas yang terdiri dari rasa hormat, berbakti, sabar, berani, jujur, dan bijaksana. Nilai sosial yang terdapat pada cerita palaya subetnika Katingan berjumlah dua puluh yang terdiri dari sikap bekerja sama, saling membantu, melakukan aktivitas bersama, membantu mengatasi kesulitan orang lain.Kata-kata kunci: nilai emosional, nilai moral, nilai sosial, cerita palaya subetnika Katingan